2000
DOI: 10.1016/s1352-2310(00)00186-2
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric volatile organic compounds (VOC) at a remote tropical forest site in central Amazonia

Abstract: According to recent assessments, tropical woodlands contribute about half of all global natural non-methane volatile organic compound (VOC) emissions. Large uncertainties exist especially about #uxes of compounds other than isoprene and monoterpenes. During the Large-Scale Biosphere/Atmosphere Experiment in Amazonia } Cooperative LBA Airborne Regional Experiment 1998 (LBA-CLAIRE-98) campaign, we measured the atmospheric mixing ratios of di!erent species of VOC at a ground station at Balbina, Amazonia. The stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
108
2
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(130 citation statements)
references
References 38 publications
13
108
2
7
Order By: Relevance
“…Deforestation and biomass burning associated with land use practices have changed convection and precipitation over the Amazon basin (Andreae et al 2004). These changes in precipitation complete a feedback loop, since the availability of water influences the amount and kind of aerosol particles that the vegetation emits (Kesselmeier et al 2000). Such interacting processes driven by change in land use and climate could reach a tipping point where the Amazon forest is replaced by savanna-like vegetation by the end of the 21 st century (Nepstad et al, 2008).…”
Section: Interactions Among the Boundariesmentioning
confidence: 99%
“…Deforestation and biomass burning associated with land use practices have changed convection and precipitation over the Amazon basin (Andreae et al 2004). These changes in precipitation complete a feedback loop, since the availability of water influences the amount and kind of aerosol particles that the vegetation emits (Kesselmeier et al 2000). Such interacting processes driven by change in land use and climate could reach a tipping point where the Amazon forest is replaced by savanna-like vegetation by the end of the 21 st century (Nepstad et al, 2008).…”
Section: Interactions Among the Boundariesmentioning
confidence: 99%
“…3 The direct contribution of biogenic emissions of HCHO and CH 3 CHO has been reported for several environments. [4][5][6] Primary sources of aldehydes are burning processes, chipboard production and chemical industry; important secondary sources are photochemical decomposition processes of hydrocarbons and other organics in the air. The incomplete combustion of oxygenated fuels in engines results in increased emissions of primary HCHO and CH 3 CHO, and consequently the formation of free radicals, ozone, carboxylic acids and peroxyacetylnitrate (PAN).…”
Section: Introductionmentioning
confidence: 99%
“…18, No. 5,2007 The major sinks of HCHO and CH 3 CHO are the chemical destruction caused by reactions with OH, HO 2 , and NO 3 , and photolysis in case of HCHO and dry deposition of HCHO and CH 3 CHO to terrestrial surfaces such as canopy surfaces and to the ground. 12 Carbonyl compounds are toxic, and their most observed toxic effects are irritation of the skin, eyes and nasopharyngeal membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of BVOC is enhanced by high reactivity with ozone (O 3 ), hydroxyl radical (OH), and nitrate radical (NO 3 ) compared to other abundant atmospheric NMVOCs, consequently BVOCs play key roles in the tropospheric chemistry of O 3 and particle formation, and in the atmospheric chemistry and physics associated with climate change. Modeling (Guenther et al, 1995) and limited measurement (Guenther et al, , 1996Kesselmeier et al, 2000;Geron et al, 2002;Greenberg et al, 2004) studies in the tropical Americas and Africa have suggested that at least 50% of the global annual BVOC flux is from tropical ecosystems, due to vast expanses (0.5-1.0 Â 10 9 ha) of evergreen vegetation and warm climate throughout the year (Guenther et al, 1995). However, very little is known of emissions from tropical Asia.…”
Section: Introductionmentioning
confidence: 99%